The Life and Afterlife of Isabeau of Bavaria - Adams, Tracy (Johns Hopkins University Press, 2010)
The fascinating history of Isabeau of Bavaria is a tale of two queens. During her lifetime, Isabeau, the long-suffering wife of mad King Charles VI of France, was respected and revered. After her death, she was reviled as an incompetent regent, depraved adulteress, and betrayer of the throne. Asserting that there is no historical support for this posthumous reputation, Tracy Adams returns Isabeau to her rightful place in history. Adulteress and traitor-two charges long leveled against the queen-are the first subjects of Adam's reinterpretation of medieval French history. Scholars have concluded that the myths of Isabeau's scandalous past are just that: rumors that evolved after her death in the context of a political power struggle. Unfortunately, this has not prevented the lies from finding their way into respected studies on the period. Adams's own work serves as a corrective, rehabilitating the reputation of the good queen and exploring the larger topic of memory and the creation of myth. Adams next challenges the general perception that the queen lacked political acumen. With her husband incapacitated by insanity, Isabeau was forced to rule a country ripped apart by feuding, power-hungry factions. Adams argues that Isabeau handled her role astutely in such a contentious environment, preserving the monarchy from the incursions of the king's powerful male relatives. Taking issue with history's harsh treatment of a woman who ruled under difficult circumstances, Adams convincingly recasts Isabeau as a respected and competent queen.